Modern trends of development at regional business in Ukraine: national traditions and international experience - Shedyakova, Tetyana (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
The article analyzes the essence of entrepreneurial processes at the regional and national levels, as well as entrepreneurial activity as a sphere of realization of economic motivation; recommendations on the improvement of the motivational mechanism of entrepreneurial activity in Ukraine are given on the example of the foreign experience. Within the framework of the article, an attempt is made to systematically comprehend the general laws of the development of entrepreneurship in a post-industrial economy and to analyze problems that related to the integration of the regional business environment into national business processes and seek ways to their solutions. The subject of research is the trends of development of regional business based on study of Ukrainian national traditions and international experience. The goal is to determinate the place and role of regional business in the national system of entrepreneurship as an actual mechanism for supporting the Ukrainian economy and its structural layers. The objective is to analyze the mistakes of an entrepreneur in the implementation of their projects and enterprises, as well as to solve problems that impede the development of business processes in the national economy. General scientific methods are used, such as: method of vertical comparisons – giving the opportunity to study the structure of phenomena and processes and trends in their change; grouping method – assumes the division of the studied set of objects into qualitatively homogeneous groups according to the corresponding characteristics; linear method – implies that the optimal variant is selected from a significant number of alternative options. The following results were obtained: the real motives of entrepreneurial activity are studied; the exceptional importance of creating new business technologies is determined; the state strategy of entrepreneurship development are obtained. Conclusions: one of the main tasks of small business support system in developed countries is to represent and protect the interests and needs of small businesses at various levels. A special feature of this process is the leading role of main government agencies and their active interaction with professional, public and other business associations. The basis of modern economic policy of the state should be in using the local and regional specifics, foreign experience in certain sectors of the economy, as well as support for education, science and private entrepreneurship.